Use of pharmaceuticals amongst athletes tested by Anti-Doping Norway in a five-year period - Gjelstad, Astrid; Herlofsen, Tine Marie; Bjerke, Anne-Linn; Lauritzen, Fredrik; Björnsdottir, Ingunn (Frontiers in Sports and Active Living, 2023)
The objective of the study was to map the use of pharmaceuticals by Norwegian athletes registered on doping control forms (DCFs) in a five-year period in order to get an overviewexamine of general and some class specific use of pharmaceuticals amongst the athletesacross sports and athlete levels. Anonymous data from doping control formsDCFs from collected in 2015-2019 were manually entered into a database using the Anatomical Therapeutic Chemical (ATC) system for classification of the pharmaceuticals. Variables entered were year of control, gender, age group, athlete level, sport/discipline, test type, nationalitynationality, and pharmaceuticals (and dietary supplements) used. The database was then used to identify commonly used pharmaceuticals as well as inappropriate use of pharmaceuticals surprising use. Pain killers in the ATC groups M01 A (NSAIDsNonsteroidal antiinflammatory drugs -NSAIDs) and N02 B (other analgetics), and anti-asthmatics in ATC groups R03 A and R03 B were the most frequently used pharmaceuticals. National level athletes reported more use of pharmaceuticals ((1.4±1.7 pharmaceuticals per form) than recreational level athletes (0.9±1.2 pharmaceuticals per form). The highest proportion of DCFs containing information about at least one pharmaceutical were found in speed skating (79.1%), alpine skiing (74.0%), rowing (72.4%) and crosscountry skiing (71.7%). Handball and football players reported use of painkillers frequentlyPainkillers were most frequently used in muscular endurance sports (30.4 % and 21.2 % for M01A and N02 B , respectively) and ball and team sports (17.9 % and 17.0 %). Use of hypnotics was reported from Iicehockey players and alpine skiers in around 8 % of the casesreported use of hypnotics surprisingly often. Use of anti-asthmatics was frequent most often reported amongst athletes specially exposed to cold, chemicals and heavy endurance training. Athletes in specialized sports requiring high levels of strength and/or endurance reported a higher use of pharmaceuticals out-of-competition compared to incompetition, while there was no such difference in complex sports, such as team, gymnastic, aiming and combat sports. The mapping revealed interesting patterns in Norwegian athletes' use of pharmaceuticals, although similarities can be found in existing literature. The ATC classification is useful for this purpose.